Teacher Resilience and Well-Being: Navigating Burnout in the Era of Educational Digitalization - Nur Ela, Nur Ela (International Journal of Social Research, 2025)
The rapid digitalization of education has brought significant changes in the dynamics of teaching, offering both opportunities and challenges. In the midst of this transformation, the resilience and well-being of teachers is a crucial factor in preventing professional burnout. The increasing use of digital platforms in teaching exacerbates stressors, which can affect teachers' mental health and job satisfaction. This phenomenon, often referred to as "teacher burnout," is a major concern in education systems around the world. This study aims to explore the impact of digitalization on teacher resilience and well-being, focusing on the factors that contribute to professional burnout and identifying strategies to reduce its impact. This study analyzes how the digitalization of education affects teacher resilience and mental health challenges faced by educators in modern classrooms. This study uses a qualitative approach with in-depth interview techniques and surveys to collect data from teachers in various educational institutions. This study analyzes factors such as digital workload, emotional power, and support systems available to teachers. Secondary data from research related to teacher burnout, resilience, and well-being were also included to provide a comprehensive analysis. Preliminary findings suggest that while digital tools have improved the efficiency of teaching practices, they have also led to increased workload and a sense of alienation among teachers. Teachers report higher levels of stress and burnout, especially in environments that do not support adequate use of digital tools. However, the presence of a strong support network, professional development programs, and personal coping strategies seems to mitigate some of the negative impacts. This research highlights the importance of targeted interventions to improve teacher well-being in the digital era. The intervention should focus on improving digital literacy, providing adequate mental health support, and building collaborative teaching communities. Schools and educational institutions must recognize the importance of teacher resilience as a cornerstone of educational success, ensuring that educators are prepared to face the challenges posed by the digitalization of education.